Efficacy of salbutamol by nebulizer versus metered dose inhaler with home-made non-valved spacer in acute exacerbation of childhood asthma - Yasmin, S; Mollah, AH; Basak, R; Islam, KT; Chowdhury, YS (Mymensingh Medical Journal, 2012)
Mymensingh Med J. 2012 Jan;21(1):66-71 The abstract of this article is available on the PubMed website